PERPLEXING IMPACTED THIRD MOLARS IN A CASE OF TRIGEMINAL NEURALGIA AND ARACHNOID CYST (CASE REPORT) - Lugito, Manuel Dwiyanto Hardjo (Universitas Baiturrahmah, 2023)
Introduction: Trigeminal neuralgia (TN) is the most frequent form of craniofacial neuropathic pain, with a wide range of severity. Trigeminal neuralgia classically has been associated with neurovascular compression in the prepontine cistern at the nerve root entry zone or in Meckel’s cave due to an abnormal vessel, tumor, or cyst. Arachnoid cysts of the posterior cranial fossa are still less commonly compared to those superior to the constituent part of the posterior cranial fossa meninges. However, the arachnoid cyst in conjunction with the impacted third molar may cause compression of the trigeminal ganglion with similar clinical symptoms. The aim of this report is to explain the management of the first division of trigeminal neuralgia with an arachnoid cyst perplexed by impacted third molars. Case report: A case of a 27-year-old female with throbbing pain on top of her head, forehead, temple, and eyes several times. Extensive clinical and radiologic examinations were performed and revealed an arachnoid cyst and impacted third molars. Impacted third molars were removed. The patient declined the surgery for the arachnoid cyst and was treated symptomatically with amitriptyline 25 mg once daily until recently. The definitive diagnosis was the first division of trigeminal neuralgia and an arachnoid cyst. Conclusions A fundamental aspect of the diagnosis of trigeminal neuralgia is to examine and exclude all possible underlying etiologies and structural pathologies, which can refer the pain to a location remote from the stimulus.